Eight new phenolic acids from the leaves of Illicium dunnianum and their osteoprotective activities. Issue 33 (4th August 2022) - Li, Hai-bo; Ma, Sen-ju; Shan, Ying-xin; Li, Ting; Wang, Zhen-zhong; Xiao, Wei; Qiu, Zuo-cheng; Yu, Yang
Abstract : Three new phenylpropenoid glycosides (1–3 ), and five undescribed shikimic acid derivatives (4–8 ), together with six known analogues (9–14 ), were obtained from the dried leaves of Illicium dunnianum . Abstract : Eight previously unreported phenolic acids (1–8 ), including three new phenylpropenoid glycosides (1–3 ), and five undescribed shikimic acid derivatives (4–8 ), together with six known analogues (9–14 ), were obtained from the dried leaves of Illicium dunnianum . The structures of these new compounds were elucidated by extensive spectroscopic analyses (1D, 2D-NMR, HRESIMS, IR, UV) and chemical methods. Compounds 1, 2, 4, and 5 were tested for their promotion effect on osteoblastogenesis of pre-osteoblastic MC3T3-E1 cells and inhibitory effect on osteoclastogenesis of RANKL-induced RAW264.7 cells. As a result, 1 and 4 exerted a promotion effect on osteoblastogenesis, but without activity on osteoclastogenesis. Our studies not only enrich the structural diversity of phenolic acids in nature, but also discover new lead compounds from folk plants with activities on osteoblastogenesis or osteoclastogenesis.